2012
DOI: 10.2319/071311-448.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface changes of anodic oxidized orthodontic titanium miniscrew

Abstract: Objective: To evaluate the structural stability of anodic oxidation treatment of miniscrews during a self-drilling procedure and an initial loading period. Materials and Methods: Eight orthodontic miniscrews with a machined surface and an anodic oxidized surface were placed in the mandible of two beagle dogs. With all miniscrews, an orthodontic force was applied immediately after placement and was continued for 12 weeks. After beagle dogs were sacrificed, the miniscrews were carefully removed from decalcified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
9
0
2
Order By: Relevance
“…Choi et al 27 evaluated the surface roughness of two different types of miniimplants and did not find any definite alteration, corroborating with our findings. However, Eliades et al 19 observed surface alterations in retrieved devices, such as loss of gloss in some parts.…”
Section: Discussionsupporting
confidence: 81%
“…Choi et al 27 evaluated the surface roughness of two different types of miniimplants and did not find any definite alteration, corroborating with our findings. However, Eliades et al 19 observed surface alterations in retrieved devices, such as loss of gloss in some parts.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, previous studies have mostly assessed miniscrews with MS. However, the use of miniscrews with treated surfaces is gradually increasing, with improved success rates 910. Therefore, we assessed both MS and ES in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among these procedures is the recently introduced anodic oxidation, which is obtained by immersion of the titanium in an electrolyte solution and by the application of high current voltage [4,5]. Upon anodic oxidation, the titanium surface is covered by a TiO 2 layer [4,5], organized in self-ordered nanotubular structures [2] vertically oriented on the titanium surface with a closed bottom and open top [6]. Notably, the greater the applied current voltage, the thicker and more rough the TiO 2 layer will be [7].…”
Section: Introductionmentioning
confidence: 99%
“…[11]), no previous studies have evaluated the behavior of commercially available products, including the effects of varying the thickness of the TiO 2 layer. Specifically, previous studies on orthodontic miniscrews are limited to the analyses of implant surfaces [5], insertion/removal torque and bone-to-implant contact sites [6][7][8].…”
Section: Introductionmentioning
confidence: 99%